PENGARUH PERPUTARAN MODAL KERJA, PERPUTARAN KAS, PERPUTARAN PIUTANG, DAN PERPUTARAN PERSEDIAAN TERHADAP PROFITABILITAS PERUSAHAAAN SUB SEKTOR FOOD AND BAVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Khairun Umrah; Nurman; Andi Mustika Amin (JURNAL BISNIS KOLEGA, 2022)
This study aims to determine the effect of working capital turnover, cash turnover, accounts receivable turnover, and inventory turnover on profitability in food and beverage sub-sector companies listed on the Indonesia Stock Exchange. The variables in this study are working capital turnover, cash turnover, accounts receivable turnover, inventory turnover (independent variable), and profitability as measured using the NPM ratio (dependent variable). The population in this study are food and beverage sub-sector companies listed on the Indonesia Stock Exchange. While the sample in this study there were 19 companies that met the sample selection criteria. Data collection using documentation techniques. the analysis technique used is the statistical method of multiple linear regression. The results showed that partially working capital turnover, cash turnover, accounts receivable turnover, and inventory turnover have a negative effect on profitability (NPM). Meanwhile, working capital turnover, cash turnover, accounts receivable turnover, and inventory turnover simultaneously have a positive effect on profitability (NPM) in food and beverage companies listed on the IDX.